Implementasi Data Mining Untuk Menentukan Persediaan Stok Pakan Kucing Menggunakan K-Means Clustering (Studi Kasus : Suterakoi) - Maulana Akbar, Fauzi; Zakaria, Hadi (CV. Shofanah Media Berkah, 2024)
Suterakoi is a company located in the Silk World. The company sells quality cat food specifically to meet the nutritional and health needs of cats. Currently the process of managing cat feed stocks in the Suterakoi warehouse continues to use conventional methods, this often leads to an inconsistency between the amount of stock available and the actual amount. Because of the lack of accurate reports on the goods sold and the availability of stocks of cat feed in the warehouse, this has resulted in a written cat feed stock report that does not correspond to the amount of cat food stock in the storehouse. This could affect customer demand for cat feed stock produced by Suterakoi. The author did a research to build a system that could help the company predict stocks of cat feed in the warehouse. For this situation, the creators run the information mining application using the K-Means Grouping strategy. This strategy is used to gather information into groups based on commonalities. by classifying stocks based on certain attributes such as product type, price, or demand needs. The author designed a web-based Data Mining application using PHP and MySQL programming languages as data storage. Hopefully this study can improve accuracy in predicting cat feed stocks.